Improved water resources management for smart farming: a case study for Cyprus - Neophytides, Stelios; Eliades, Marinos; Mavrovouniotis, Michalis; Papoutsa, Christiana; Papadavid, George; Hadjimitsis, Diofantos G. (My University, 2024)
Water-scarce areas are threatened by climate crisis and, thus, there is an urgent need for optimizing water resources management. Remote sensing has been widely used for calculating the evapotranspiration over large areas, which is an essential variable for calculating the actual irrigation needs of crops. The main objective of this work is to design an approach to optimize the irrigation needs for specific crops. The island of Cyprus is used as a case study providing first insights for water management in the country. The proposed approach is crucial to the agricultural industry of Cyprus since it is located in the Mediterranean region which is affected by warm climate and drought events. Specifically, the proposed approach calculates daily the crop evapotranspiration over the island for three of the most important crops (i.e., citrus, olives, and potatoes) cultivated in Cyprus. The results of this study are showing that the three crop types are withdrawing much more water than the total annual inflow of reservoirs in 2023. Therefore, better irrigation management needs to be adopted by farmers while optimized water resources management practices have to be embraced by local authorities and stakeholders.
Keywords: Evapotranspiration; Water Management; Agriculture; Climate crisis; Remote Sensing